Research Progress on Vitiligo and Its Comorbidities - Hu, Haoyuan; Yan, Xiaoning (Journal of Contemporary Medical Practice, 2024)
Vitiligo is a chronic acquired depigmentation skin disease, the pathogenesis of vitiligo is not clear, previously, clinicians usually regarded vitiligo as a simple skin disease, but more and more research evidence shows that vitiligo patients are more likely to have autoimmune diseases, psychological diseases and other diseases than the general population. Therefore, this article classifies vitiligo and related diseases, and elaborates its possible pathogenesis, to provide a basis for further research on vitiligo and its comorbidities.